Bacillus velezensis 20507 promotes symbiosis between Bradyrhizobium japonicum USDA110 and soybean by secreting flavonoids - Cheng, Yunqing; Jiang, Xingtong; He, Xinyi; Wu, Zhaoyang; Lv, Qiang; Zhao, Shuang; Zhang, Xinyue; Wang, Shuai; He, Hongli; Liu, Jianfeng (Frontiers in Microbiology, 2025)
IntroductionWhile co-inoculation with rhizobia and plant growth-promoting rhizobacteria (PGPR) can enhance soybean growth and nodulation, the interaction mechanisms between Bacillus velezensis 20507 and Bradyrhizobium japonicum USDA110 under varying nitrogen (N) supply levels (0–10 mmol/L) remain unclear. This study investigates how their synergistic interactions influence soybean nitrogen content per plant and molecular pathways.MethodsSoybean plants were co-inoculated with B. velezensis and B. japonicum across four N levels. Nodulation, plant growth, physiology, and N content were quantified. Transcriptome sequencing of soybean roots under N deficiency compared single and co-inoculation treatments. Flavonoids in B. velezensis fermentation broth were identified via mass spectrometry, and rutin’s regulatory effects on B. japonicum nodulation genes (NodD1/NodD2) were tested in coculture.ResultsCo-inoculation significantly increased nodulation, biomass, and N content per plant compared to single inoculations across all N levels. Under N deficiency, co-inoculation induced 5,367 differentially expressed genes (DEGs), with Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment in phenylpropanoid (ko00940) and flavonoid biosynthesis (ko00941). B. velezensis produced 29 flavonoids and 4 isoflavonoids (including rutin). Rutin (5–10 mg/L) upregulated NodD1 and suppressed NodD2 in B. japonicum.DiscussionB. velezensis enhances B. japonicum-soybean symbiosis via flavonoid secretion, particularly rutin, which modulates nodulation gene expression. This metabiotic interaction improves soybean N assimilation and growth, even under low N conditions. The findings provide a foundation for designing composite inoculants to optimize soybean yield and nitrogen-use efficiency.